The Application of Jurisprudential Inquiry Learning Model to Improve Students' Social Sensitivity and Learning Achievement - Lamtiur Tampubolon (CV. Media Inti Teknologi, 2022)
Jurisprudential Inquiry, is problem-solving orientated learning, especially related to the application of learning materials in real life. As long as students do problem-solving activities. Jurisprudential Inquiry will run effectively, if the application of learning centres on student activities, namely by developing students' ability to solve problems in real life (contextual), fostering reflective thinking, helping development in the active involvement of students in the learning process. The objectives of this study are: 1) Describing the application of the Jurisprudential Inquiry learning model can increase students' social sensitivity at SMA N 2 Bengkulu Utara. 2) Describing the application of the Jurisprudential Inquiry learning model can improve student learning achievement at SMA N 2 Bengkulu Utara. 3) Describe the application of the Jurisprudential Inquiry learning model can improve student learning achievement at SMA N 2 Bengkulu Utara. The research was conducted at SMA N 2 Bengkulu Utara on 23-25 January 2023. The research sample was XI IPS 1 and 2 class students with a total population of 50 people. Sampling technique using simple random sample research method. quantitative. The research instrument was carried out by classroom action research followed by a quasi-experiment by comparing the treatment of two different classes between the control class and the experimental class. Data collection techniques in this study used subject teacher observation data and questionnaires. The instrument used is an observation instrument sheet, questionnaire analysis Data analysis techniques using a Likert scale.Based on the results of observations and questionnaire results that students want a variety of learning models, one of which is the Jurisprudential Inquiry model.